Raymond Williams - Richard Wyatt (PRISM)
This paper highlights the continued relevance of the working-class academic Raymond Williams (31 August 1921 – 26 January 1988) to today’s students and academics. It will do this by introducing Williams and his key ideas in the form of a short think piece. This overview can be used to compliment more in-depth studies for seeking to understand social phenomena. The key concepts introduced within this paper focus on, culture as a whole way of life, ‘structure of feeling’, Williams’ debate with Marxism, historical analysis and his approaches to methodology.